2003
DOI: 10.1051/forest:2003062
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of vegetation control treatments for release of Engelmann spruce from a mixed-shrub community in Southern British Columbia

Abstract: -In British Columbia, vegetation management treatments are widely used to ensure successful establishment of young stands and achievement of free-growing requirements. A study was established in 1991 to examine the effectiveness of vegetation control treatments for release of Engelmann spruce (Picea engelmannii Parry) seedlings from a mixed-shrub community. The study consisted of eight treatments replicated three times in a completely randomized design. The treatments comprised six combinations of spring, summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 18 publications
5
31
1
Order By: Relevance
“…Future measurements will be needed to confirm this observation. Results from other spruce vegetation management studies [3,30] have also indicated that longerterm observations may differ from early results, emphasizing the importance of longer-term studies when evaluating vegetation management treatments.…”
Section: Discussionmentioning
confidence: 94%
“…Future measurements will be needed to confirm this observation. Results from other spruce vegetation management studies [3,30] have also indicated that longerterm observations may differ from early results, emphasizing the importance of longer-term studies when evaluating vegetation management treatments.…”
Section: Discussionmentioning
confidence: 94%
“…If left untreated this mixed-shrub complex can reduce survival and growth of planted spruce through reduction in light levels and induced vegetation and snow press. Significant improvement in spruce survival was noted for the repeated manual brushing and glyphosate treatments; however, significant height growth differences were limited to years 4 to 5 and diameter growth to years 3 to 7 post-treatment (Biring et al 2003).…”
Section: Methodsmentioning
confidence: 97%
“…The 10-year post-treatment results from these two trials have been previously published (Biring et al 2003, Harper et al 2005 and represent some of the oldest stand-level, vegetation management datasets presently available from British Columbia. The objectives of this paper are to explore the long-term growth and yield predictions for the various vegetation management treatments and to compare the TASS results in terms of merchantable volume, physical rotation age and stand productivity.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations